Partially Lithiated Microscale Silicon Particles as Anode Material for High-Energy Solid-State Lithium-Ion Batteries - Poetke, Stephanie; Cangaz, Sahin; Hippauf, Felix; Haufe, Stefan; Doerfler, Susanne; Althues, Holger; Kaskel, Stefan (Energy Technology, 2023)
The high gravimetric and volumetric capacity of silicon renders it an attractive anode material for lithium-ion solid-state batteries (SSBs). Herein, the partial lithiation (800 mAh g−1) of cost-attractive silicon microparticles (μm-Si) in half- and full cells versus nickel–rich NCM (LiNi0.9Co0.05Mn0.05O2) with Li6PS5Cl as a solid electrolyte (SE) is investigated. As a consequence of the cathode and anode potential curve evolution determined in a three-electrode SSB cell, the charge cut-off potential of the NCM|SE|μm–Si cells is reduced. Thereby, the capacity retention after 50 cycles is more than doubled from 32% to 71% without active pressure control on the cells. This concept addresses both the volume changes and the availability of the anode material on an industrial scale being necessary for the utilization of silicon anodes for electric vehicles and other applications. NCM|SE|μm-Si cells achieve up to 28% higher volumetric energy densities compared to the conventional graphite anode.
CRIS-Team Scopus Importer:2023-03-20
Keywords: lithium-ion solid-state batteries; microscale silicon particles; partial lithiation; thiophosphate solid electrolytes